How to arrange distance education using on-line platforms? - Krut, Yu. Ya.; Siusiuka, V.; Puchkov, V.; Izbytska, N.; Pavlychenko, D.; Круть, Юрій Якович; Сюсюка, Володимир Григорович; Пучков, Володимир Анатолійович; Ізбицька, Ніна Григорівна (Гродно, 2020)
The current and transient trends of the educational space impose certain pedagogical requirements on the higher education institution teacher. Firstly, it means the ability to work with students effectively and remotely, also, to be familiar with technology and media literacy, as that is 21st century important educational skills. Nowadays, every teacher in Ukraine has a question: how to arrange students distance education in the long-term quarantine? Let’s consider the tools for distance learning that will allow you to organize the educational process for students and teachers. The objective is not only to provide the study material, but also to assist and track the students' learning process. In addition, to support the motivation of students during quarantine, the process of learning must be interactive.